The Role of Pronouns in Malay Grammar and Differences Usage of Pronouns between English and Malay Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this scientific article describes the types of adjective that uses in the grammar of the malay language, their place in the sentence is clearly explained, and based on the findings, similarities and differences with the grammar of the english language are explained through opinions and analyzes.